Lubricating oil as well as preparation method and application thereof

The modified TiO2/graphene composite material in lubricating oils addresses the limitations of traditional base oils by enhancing dispersibility and wear resistance, forming a strong lubricating film, and adsorbing harmful substances, thereby improving stability and reducing friction.

CN119242372APending Publication Date: 2025-01-03RITUI ENERGY TECH HEBEI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424879.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional lubricating oils face challenges in high wear resistance and stability due to the poor performance of base oils and the difficulty of dispersing graphene additives, which limits their effectiveness in modern industrial applications.

Method used

A lubricating oil formulation incorporating a modified TiO2/graphene composite material, prepared through specific steps including the mixing of polyethyleneimine, acetic acid, and tetrabutyl titanate, followed by ultrasonic dispersion, spray drying, and thermal reduction, enhances the dispersibility and wear resistance of the lubricant.

Benefits of technology

The modified TiO2/graphene composite material improves the lubricating oil's stability and wear resistance by forming a strong lubricating film, reducing friction and wear, and adsorbing harmful substances, thus extending its service life and environmental compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of lubricating oil, and provides lubricating oil as well as a preparation method and application thereof. The lubricating oil is prepared from the following raw materials in parts by weight: 70 to 80 parts of base oil, 2 to 3 parts of a modified TiO2 / graphene composite material, 0.1 to 0.3 part of a de-foaming agent, 0.4 to 0.6 part of an antioxidant, 2 to 3 parts of an anti-rust agent and 1 to 1.2 parts of a calcium detergent, the preparation method of the modified TiO2 / graphene composite material comprises the following steps: (1) preparing mesoporous TiO2; (2) preparing a TiO2 / graphene composite material; and (3) preparing the modified TiO2 / graphene composite material: dispersing the TiO2 / graphene composite material in an ethanol aqueous solution, adding 3-aminopropyltriethoxysilane, then carrying out an ultrasonic reaction, and after the reaction is finished, washing and drying to obtain the modified TiO2 / graphene composite material. According to the lubricating oil provided by the invention, by optimizing the raw material ratio and the preparation process, the stability and wear resistance of the lubricating oil are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lubricating oils, and in particular to a lubricating oil and a preparation method and application thereof. Background Art

[0002] As an important component of industrial production, lubricating oil is widely used in various mechanical equipment to reduce friction, protect machinery and processed parts, and play an important role in controlling friction, reducing wear, cooling, sealing and isolation. With the continuous advancement of industrial technology and the enhancement of environmental awareness, the requirements for lubricating oil performance are also increasing.

[0003] Traditional lubricants are mainly composed of base oil and additives, of which base oil accounts for the vast majority. However, the base oil itself has poor performance in different working environments and limited load-bearing capacity, making it difficult to meet the requirements of modern industry for high wear resistance and high stability.

[0004] In order to improve the performance of base oil, specific additives are usually added. As a material with a unique two-dimensional structure, ultra-high elastic modulus, fracture strength and thermal conductivity, graphene has shown great potential in the field of lubricant additives. However, there are van der Waals forces between graphene sheets, which are easy to agglomerate, making it difficult to fully disperse in lubricating oil and unable to give full play to its excellent physical and chemical properties. Based on this, the present invention provides a lubricating oil and its preparation method and application. Summary of the invention

[0005] The present invention provides a lubricating oil and a preparation method and application thereof, and improves the stability and wear resistance of the lubricating oil by optimizing the raw material ratio and the preparation process.

[0006] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a lubricating oil comprising the following raw materials in parts by weight: 70-80 parts of base oil, 2-3 parts of modified TiO2 / graphene composite material, 0.1-0.3 parts of defoamer, 0.4-0.6 parts of antioxidant, 2-3 parts of rust inhibitor, 1-1.2 parts of calcium detergent; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Mix polyethyleneimine, acetic acid and tetrabutyl titanate and grind them, then heat treat to obtain TiO2; (2) Preparation of TiO2 / graphene composite material: ultrasonically dispersing graphene oxide and TiO2 in deionized water to obtain a dispersion, spray drying the dispersion, and then subjecting the dispersion to a high-temperature thermal reduction reaction; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material is dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane is added and then ultrasonically reacted, and after the reaction is completed, the composite material is washed and dried.

[0007] As a further technical solution, the usage ratio of polyethyleneimine, acetic acid and tetrabutyl titanate is (0.5-0.6) g: (0.8-1.2) mL: (2-2.4) g.

[0008] As a further technical solution, the heat treatment is carried out in an air atmosphere at a temperature of 420-440° C. for 50-60 minutes.

[0009] As a further technical solution, the usage ratio of the graphene oxide, TiO2 and deionized water is (2-3) g: (6-8) g: (850-950) mL.

[0010] As a further technical solution, the spray drying feed temperature is 150-160°C, the discharge temperature is 70-80°C, and the spray drying time is 1.5-2.5h.

[0011] As a further technical solution, the high temperature thermal reduction reaction temperature is 260-280°C and the reaction time is 60-70 minutes.

[0012] As a further technical solution, the weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane is (0.4-0.6):(5-6):(14-15):(0.25-0.3); and the ultrasonic reaction time is 200-220 min.

[0013] As a further technical solution, the base oil includes polyalphaolefin and bio-base oil in a weight ratio of (5-6): (1-2); the bio-base oil includes any one of soybean oil, sunflower oil and rapeseed oil.

[0014] As a further technical solution, the defoaming agent is tributyl phosphate; the antioxidant is RF5057 or RF5067; the rust inhibitor is sodium sulfonate, and the calcium-based detergent is calcium sulfonate.

[0015] In a second aspect, the present invention proposes a method for preparing a lubricating oil, comprising the steps of: stirring and mixing the base oil, adding a modified TiO2 / graphene composite material at a temperature of 40-50°C, stirring for 10-15 minutes at a rotation speed of 400-500r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 60-80 minutes, stopping stirring and naturally cooling to room temperature.

[0016] In a third aspect, a lubricating oil provided by the present invention is applied to automobile engines or mechanical equipment.

[0017] The working principle and beneficial effects of the present invention are: 1. The polyalphaolefin in the present invention has excellent thermal stability and oxidation stability, while the bio-based oil (such as soybean oil, sunflower oil, rapeseed oil) provides good lubricity and biodegradability. The combination of the two can ensure the stability of the lubricating oil under high temperature and high pressure to a certain extent, and can also reduce pollution to the environment; 2. The graphene in the modified TiO2 / graphene composite material of the present invention has extremely high strength and wear resistance. After being compounded with TiO2, a synergistic effect can be formed to improve the wear resistance of the lubricant. After further modification, the dispersibility of the TiO2 / graphene composite material can be improved to prevent the additive from agglomerating in the base oil, thereby enhancing the compatibility of the TiO2 / graphene composite material with the lubricant base oil, making it easier to disperse in the lubricant to form a stable lubrication system; and the modified TiO2 / graphene composite material can form a stronger lubricating film in the lubricant, effectively reducing friction and wear, and improving the wear resistance of the lubricant.

[0018] 3. The modified TiO2 / graphene composite material in the present invention will flow with the lubricating oil and contact the friction pair surface. Due to the high specific surface area of ​​graphene, it is easily adsorbed onto the friction pair surface to form a preliminary adsorption layer. At the same time, TiO2 nanoparticles will also be deposited on the friction pair surface to form a composite deposition layer with graphene, thereby forming a solid lubricating film on the friction pair surface. This lubricating film can reduce the direct contact between the friction pairs, thereby reducing the friction coefficient and wear rate.

[0019] 4. The TiO2 in the modified TiO2 / graphene composite material of the present invention has a mesoporous structure, and the high specific surface area of ​​graphene can adsorb and decompose harmful substances in lubricating oil, such as free radicals, metal ions, etc. This helps to extend the service life of the lubricating oil and improve its stability. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The present invention provides a lubricating oil, comprising the following raw materials in parts by weight: 70-80 parts of base oil, 2-3 parts of modified TiO2 / graphene composite material, 0.1-0.3 parts of defoamer, 0.4-0.6 parts of antioxidant, 2-3 parts of rust inhibitor, 1-1.2 parts of calcium detergent; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Mix polyethyleneimine, acetic acid and tetrabutyl titanate and grind them, then heat treat to obtain TiO2; (2) Preparation of TiO2 / graphene composite material: ultrasonically dispersing graphene oxide and TiO2 in deionized water to obtain a dispersion, spray drying the dispersion, and then subjecting the dispersion to a high-temperature thermal reduction reaction; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material is dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane is added and then ultrasonically reacted, and after the reaction is completed, the composite material is washed and dried.

[0022] The present invention can also add other additives based on this solution. This solution is further described below: Example 1 In this embodiment, a lubricating oil is provided, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of modified TiO2 / graphene composite material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust inhibitor sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 430°C for 55 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.55 g:1 mL:2.2 g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, spray dry the dispersion, the spray drying feed temperature is 155°C, the discharge temperature is 75°C, and the spray drying time is 2h; then carry out a high-temperature thermal reduction reaction to obtain the composite material; the high-temperature thermal reduction reaction temperature is 270°C, and the reaction time is 65min; the amount ratio of graphene oxide, TiO2 and deionized water is 2.5g:7g:900mL; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material was dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane was added and then subjected to ultrasonic reaction for 210 min. After the reaction, the mixture was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane was 0.5:5.5:14.5:0.27. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0023] Example 2 In this embodiment, a lubricating oil is provided, which is composed of the following raw materials in parts by weight: 70 parts of base oil, 2 parts of modified TiO2 / graphene composite material, 0.1 parts of defoaming agent tributyl phosphate, 0.4 parts of antioxidant RF5057, 2 parts of rust inhibitor sodium sulfonate, 1 part of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and sunflower oil in a weight ratio of 5:1; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 420°C for 50 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.5g:0.8mL:2g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, spray dry the dispersion, the spray drying feed temperature is 150°C, the discharge temperature is 70°C, and the spray drying time is 1.5h; then carry out a high-temperature thermal reduction reaction to obtain the composite material; the high-temperature thermal reduction reaction temperature is 260°C, and the reaction time is 60min; the amount ratio of graphene oxide, TiO2 and deionized water is 2g:6g:850mL; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material was dispersed in an ethanol-water solution, 3-aminopropyltriethoxysilane was added and then subjected to ultrasonic reaction for 200 min. After the reaction, the mixture was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane was 0.4:5:14:0.25. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 40°C, stirring for 10 minutes at a rotation speed of 400 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 60 minutes, stopping stirring and naturally cooling to room temperature.

[0024] Example 3 In this embodiment, a lubricating oil is provided, which is composed of the following raw materials in parts by weight: 80 parts of base oil, 3 parts of modified TiO2 / graphene composite material, 0.3 parts of defoaming agent tributyl phosphate, 0.6 parts of antioxidant RF5067, 3 parts of rust inhibitor sodium sulfonate, 1.2 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and rapeseed oil in a weight ratio of 3:1; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 440°C for 60 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.6 g:1.2 mL:2.4 g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, spray dry the dispersion, the spray drying feed temperature is 160°C, the discharge temperature is 80°C, and the spray drying time is 2.5h; then carry out a high-temperature thermal reduction reaction to obtain the composite material; the high-temperature thermal reduction reaction temperature is 280°C, and the reaction time is 70min; the amount ratio of graphene oxide, TiO2 and deionized water is 3g:8g:950mL; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material was dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane was added and then ultrasonically reacted for 220 min. After the reaction, the mixture was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane was 0.6:6:15:0.3. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 50°C, stirring for 15 minutes at a rotation speed of 500 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 80 minutes, stopping stirring and naturally cooling to room temperature.

[0025] Example 4 In this embodiment, a lubricating oil is provided, which is composed of the following raw materials in parts by weight: 70 parts of base oil, 3 parts of modified TiO2 / graphene composite material, 0.1 parts of defoaming agent tributyl phosphate, 0.6 parts of antioxidant RF5067, 2 parts of rust inhibitor sodium sulfonate, 1.2 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and rapeseed oil in a weight ratio of 5:2; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 420°C for 60 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.5g:1.2mL:2g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, spray dry the dispersion, the spray drying feed temperature is 160°C, the discharge temperature is 70°C, and the spray drying time is 2.5h; then carry out a high-temperature thermal reduction reaction to obtain the composite material; the high-temperature thermal reduction reaction temperature is 260°C, and the reaction time is 70min; the amount ratio of graphene oxide, TiO2 and deionized water is 2g:8g:850mL; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material was dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane was added and then subjected to ultrasonic reaction for 220 min. After the reaction, the mixture was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane was 0.4:6:14:0.3. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 40-50°C, stirring for 10-15 minutes at a rotation speed of 400-500r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 60-80 minutes, stopping stirring and naturally cooling to room temperature to obtain the lubricating oil.

[0026] Comparative Example 1 A lubricating oil is provided in this comparative example, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of modified TiO2 / graphene composite material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust inhibitor sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 430°C for 55 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.55 g:1 mL:2.2 g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, spray dry the dispersion, the spray drying feed temperature is 155°C, the discharge temperature is 75°C, and the spray drying time is 2h; then carry out a high-temperature thermal reduction reaction to obtain the composite material; the high-temperature thermal reduction reaction temperature is 270°C, and the reaction time is 65min; the amount ratio of graphene oxide, TiO2 and deionized water is 2.5g:7g:900mL; (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material was dispersed in an ethanol-water solution, 3-aminopropyltriethoxysilane was added, and then an ultrasonic reaction was carried out for 210 minutes. After the reaction, it was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the TiO2 / graphene composite material, ethanol, water and γ-glycidyloxypropyltrimethoxysilane was 0.5:5.5:14.5:0.27. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0027] Comparative Example 2 A lubricating oil is provided in this comparative example, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of TiO2 / graphene composite material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust inhibitor sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 430°C for 55 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.55 g:1 mL:2.2 g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, spray dry the dispersion, the spray drying feed temperature is 155°C, the discharge temperature is 75°C, and the spray drying time is 2h; then carry out a high-temperature thermal reduction reaction to obtain the composite material; the high-temperature thermal reduction reaction temperature is 270°C, and the reaction time is 65min; the amount ratio of graphene oxide, TiO2 and deionized water is 2.5g:7g:900mL; The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the TiO2 / graphene composite material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding a defoamer, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing stirring for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0028] Comparative Example 3 A lubricating oil is provided in this comparative example, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of modified graphene material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust preventive sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of graphene material: ultrasonically dispersing graphene oxide in deionized water to obtain a dispersion, spray drying the dispersion, the spray drying feed temperature is 155°C, the discharge temperature is 75°C, and the spray drying time is 2h; then high-temperature thermal reduction reaction is performed to obtain the graphene material; the high-temperature thermal reduction reaction temperature is 270°C, and the reaction time is 65min; the amount ratio of graphene oxide to deionized water is 2.5g:900mL; (2) Preparation of modified graphene composite material: The graphene composite material is dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane is added and then ultrasonically reacted for 210 minutes. After the reaction, it is washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane is 0.5:5.5:14.5:0.27. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified graphene material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0029] Comparative Example 4 A lubricating oil is provided in this comparative example, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of modified TiO2 / graphene composite material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust inhibitor sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 430°C for 55 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.55 g:1 mL:2.2 g; (2) Preparation of TiO2 / graphene composite material: ultrasonically disperse graphene oxide and TiO2 in deionized water to obtain a dispersion, and spray dry the dispersion to obtain a TiO2 / graphene composite material. The feed temperature of the spray drying is 155°C, the discharge temperature is 75°C, and the spray drying time is 2 h. The amount ratio of graphene oxide, TiO2 and deionized water is 2.5 g:7 g:900 mL. (3) Preparation of modified TiO2 / graphene composite material: The TiO2 / graphene composite material was dispersed in an ethanol aqueous solution, 3-aminopropyltriethoxysilane was added and then subjected to ultrasonic reaction for 210 min. After the reaction, the mixture was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane was 0.5:5.5:14.5:0.27. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0030] Comparative Example 5 A lubricating oil is provided in this comparative example, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of modified TiO2 material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust inhibitor sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of modified TiO2 material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 430°C for 55 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.55 g:1 mL:2.2 g; (2) Preparation of modified TiO2 material: TiO2 was dispersed in an ethanol-water solution, 3-aminopropyltriethoxysilane was added and then ultrasonically reacted for 210 min. After the reaction, it was washed three times with anhydrous ethanol and dried at 80°C. The weight ratio of TiO2, ethanol, water and 3-aminopropyltriethoxysilane was 0.5:5.5:14.5:0.27. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding the defoaming agent, antioxidant, rust inhibitor and calcium detergent and continuing stirring for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0031] Comparative Example 6 A lubricating oil is provided in this comparative example, which is composed of the following raw materials in parts by weight: 75 parts of base oil, 2.5 parts of modified TiO2 / graphene composite material, 0.2 parts of defoaming agent tributyl phosphate, 0.5 parts of antioxidant RF5057, 2.5 parts of rust inhibitor sodium sulfonate, 1.1 parts of calcium detergent calcium sulfonate; The base oil includes polyalphaolefin and soybean oil in a weight ratio of 5.5:1.5; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: (1) Preparation of mesoporous TiO2: Polyethyleneimine, acetic acid and tetrabutyl titanate were mixed and ground for 8 minutes, and heat treated at 430°C for 55 minutes to obtain TiO2; the amount ratio of polyethyleneimine, acetic acid and tetrabutyl titanate was 0.55 g:1 mL:2.2 g; (2) Preparation of graphene material: ultrasonically dispersing graphene oxide in deionized water to obtain a dispersion, spray drying the dispersion, the spray drying feed temperature is 155°C, the discharge temperature is 75°C, and the spray drying time is 2h; then high-temperature thermal reduction reaction is performed to obtain the graphene material; the high-temperature thermal reduction reaction temperature is 270°C, and the reaction time is 65min; the amount ratio of graphene oxide to deionized water is 2.5g:900mL; (3) Preparation of modified TiO2 / graphene composite materials: TiO2 and graphene materials were dispersed in an ethanol-water solution, 3-aminopropyltriethoxysilane was added, and then ultrasonic reaction was carried out for 210 minutes. After the reaction, it was washed with anhydrous ethanol for 3 times and dried at 80°C. The weight ratio of TiO2, graphene material, ethanol, water and 3-aminopropyltriethoxysilane was 0.13:0.37:5.5:14.5:0.27. The preparation method of the lubricating oil comprises the following steps: stirring and mixing the base oil, adding the modified TiO2 / graphene composite material at a temperature of 45°C, stirring for 12 minutes at a rotation speed of 450 r / min, then adding a defoaming agent, an antioxidant, a rust inhibitor and a calcium-based detergent and continuing to stir for 70 minutes, stopping stirring and naturally cooling to room temperature.

[0032] Test Example 1: The lubricating oils prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-6 were tested, and the results are shown in Table 1 below: Table 1

[0033] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lubricating oil, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of base oil, 2-3 parts of modified TiO2 / graphene composite material, 0.1-0.3 parts of defoamer, 0.4-0.6 parts of antioxidant, 2-3 parts of rust inhibitor, 1-1.2 parts of calcium detergent; Wherein, the preparation method of the modified TiO2 / graphene composite material comprises: S1. Preparation of mesoporous TiO2: Mix polyethyleneimine, acetic acid and tetrabutyl titanate and grind them, and then heat treat to obtain TiO2; S2. preparing a TiO2 / graphene composite material: ultrasonically dispersing graphene oxide and TiO2 in deionized water to obtain a dispersion, spray drying the dispersion, and then performing a thermal reduction reaction to obtain a dispersion; S3. Preparation of modified TiO2 / graphene composite material: dispersing the TiO2 / graphene composite material in an ethanol aqueous solution, adding 3-aminopropyltriethoxysilane and conducting ultrasonic reaction, and washing and drying after the reaction.

2. A lubricating oil according to claim 1, characterized in that: The usage ratio of polyethyleneimine, acetic acid and tetrabutyl titanate is 0.5-0.6 g: 0.8-1.2 mL: 2-2.4 g.

3. The lubricating oil according to claim 1, characterized in that: The heat treatment is carried out in an air atmosphere at a temperature of 420-440° C. for 50-60 minutes.

4. A lubricating oil according to claim 1, characterized in that: The usage ratio of the graphene oxide, TiO2 and deionized water is 2-3g:6-8g:850-950mL.

5. The lubricating oil according to claim 1, characterized in that: The feed temperature of the spray drying is 150-160°C, the discharge temperature is 70-80°C, and the spray drying time is 1.5-2.5h; the temperature of the thermal reduction reaction is 260-280°C, and the time is 60-70min.

6. The lubricating oil according to claim 1, characterized in that: The weight ratio of the TiO2 / graphene composite material, ethanol, water and 3-aminopropyltriethoxysilane is 0.4-0.6:5-6:14-15:0.25-0.3; and the ultrasonic reaction time is 200-220 minutes.

7. The lubricating oil according to claim 1, characterized in that: The base oil comprises polyalphaolefin and bio-base oil in a weight ratio of 5-6:1-2; the bio-base oil comprises any one of soybean oil, sunflower oil and rapeseed oil.

8. The lubricating oil according to claim 1, characterized in that: The defoaming agent is tributyl phosphate; the antioxidant is RF5057 or RF5067; the rust inhibitor is sodium sulfonate, and the calcium-based detergent is calcium sulfonate.

9. A method for preparing a lubricating oil according to any one of claims 1 to 8, characterized in that the steps include: The base oil is stirred and mixed, and the modified TiO2 / graphene composite material is added at a temperature of 40-50°C, and stirred at a speed of 400-500r / min for 10-15min. Subsequently, a defoamer, an antioxidant, a rust inhibitor and a calcium-based detergent are added and stirring is continued for 60-80min. After stopping stirring, the mixture is naturally cooled to room temperature.

10. Use of the lubricating oil according to any one of claims 1 to 8, characterized in that: The lubricating oil is applied to automobile engines or mechanical equipment.